The long-run share price performance resulting from mergers & acquisitions in South Africa: a calendar-time approach - Lumala, Arnold (Department of Finance and Tax, 2020)
With increasing globalisation and the need to expand into new markets quickly and efficiently, South African firms are more than ever relying on mergers and acquisitions (M&A). It is therefore important to revisit the debate on whether M&A is a beneficial long-term corporate strategy for shareholders, especially given that little South African literature exists on this issue. This study addresses this question by examining both the short- and long-run share return performances resulting from 204 mergers and acquisitions (M&A) over the period 2003-2014, involving companies listed on the Johannesburg Stock Exchange (JSE) as acquirers. The measurement of long-run performance of M&A and other corporate events such as share buy backs and seasoned offerings remains contentious primarily due to concerns on the appropriate benchmarks for abnormal share return performance as a result of these events and the methodology used to measure long-run realized returns from these events. With regard to benchmarks, a combination of four return factors deemed appropriate for the South African equity market is used to benchmark the abnormal returns related to M&A activities. These factors are the JSE’s Financial & Industrials Index (JSE index code J213 or colloquially known as the Findi), the JSE’s Resources Index (JSE index code J210 or colloquially known as the Resi), and the size and book-to-market factors. Two methods have been widely used to determine the long-run share return performance from corporate events: The Buy-and-Hold Abnormal Return (BHAR) approach and the more statistically robust Calendar Time Portfolio (CTP) approach. Using these two approaches, this study finds that, in the long term, there are no statistically significant abnormal returns associated with merger and acquisition transactions for the sample of South African acquirers tested. The correlation of a number of key transaction attributes with long-run M&A related share return performance is also examined in this study. The following characteristics are thus tested: the method of payment (cash, equity or cash and equity), the listing status of acquisition targets (private, public or subsidiary), the target’s geographical location (cross-border or non-cross border, i.e. South African), the relatedness of the target’s industry to the acquirer’s (i.e. conglomerate versus horizontal M&A) and the percentage of the target acquired (50% or more and less than 50%). The results indicate that cash acquirers outperform both equity and cash and equity acquirers, acquirers of subsidiaries outperform acquirers of private or public targets, cross-border acquirers outperform non cross-border acquirers, conglomerate M&A underperform horizontal or related M&A and gaining control, i.e. acquiring 50% or more of the target results in slightly higher return than not gaining control. In addition, the short-run share return performance of M&A is examined to investigate whether investors’ short-run expectations from M&A announcements manifest in the long-run. The findings indicate that a positive abnormal short-run return is on average achieved in the -5, 5 event window. However, the market corrects for this initial positive reaction to M&A announcements, as the positive return becomes insignificant within 10 days of the announcement. The results of this study indicate that South African companies’ merger and acquisition activities do not deliver any statistically significant short- or long-term value to shareholders, implying that great care should be taken when considering such actions.